Molecular Epidemiology and Antimicrobial Resistance in Uropathogenic Escherichia coli in Saudi Arabian Healthcare Facilities - Mateq Ali Alreshidi (Microbiology Research)
Urinary tract infections (UTIs) caused by uropathogenic Escherichia coli (UPEC) are a major healthcare challenge, necessitating effective antimicrobial therapy for treatment. However, the prevalence of antimicrobial resistance among UPEC strains is escalating, particularly among patients experiencing recurrent infection. The rise in UPEC strains that exhibit resistance to multiple antimicrobial agents, including the spread of extended-spectrum beta-lactamase (ESBL)-producing UPEC, intensifies the complexity of managing UTIs. Genetic variations within UPEC strains play a major role in their ability to resist antimicrobial agents and adapt to changing environments. Unveiling and understanding the genomic landscape of emerging UPEC strains is essential for comprehending the genetic basis of their resilience. Moreover, monitoring these genetic strains is crucial for identifying patterns of resistance dissemination, guiding infection control measures, and informing the development of targeted therapeutics.